2007
DOI: 10.2319/091906-378
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Orthognathic Surgery in Chinese Patients

Abstract: Objective: To evaluate the outcome of orthognathic surgery by objective cephalometric measurement of posttreatment soft-tissue profile and by subjective evaluation of profile esthetics by laypersons and clinicians. Materials and Methods: The sample consisted of 30 Chinese patients who had completed combined orthodontic and orthognathic surgical treatment. The posttreatment cephalograms of these patients were analyzed with respect to profile convexity, facial height, and lip contours and these were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…However, this is not in agreement with our findings. The present results are in accordance with the study of Chew et al (36) which was based on cephalograms and showed that lower facial height did not significantly influence profile aesthetics as evaluated by clinicians and laypersons. According to a facial silhouette study, lower facial height has an influence on frontal facial attractiveness perception of laypersons (17).…”
Section: Discussionsupporting
confidence: 93%
“…However, this is not in agreement with our findings. The present results are in accordance with the study of Chew et al (36) which was based on cephalograms and showed that lower facial height did not significantly influence profile aesthetics as evaluated by clinicians and laypersons. According to a facial silhouette study, lower facial height has an influence on frontal facial attractiveness perception of laypersons (17).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, based on our results, the correction of a deviation is not always going to perfect a smile, according to the evaluations of laypeople. Some studies show that laypeople accept a wider range of deviation compared to dentists, 7,8 and because of this a dentist must be careful about imposing his or her own beauty norms upon patients.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Currently, a consensus on the levels of acceptability of different variations from esthetic norms does not ex- ist, and there is not even an accepted hierarchy of the influence of different esthetic norms. Knowledge in this area will aid the choice of treatments and increase the chances of clinical success.…”
Section: Introductionmentioning
confidence: 99%
“…This accentuates the importance of understanding the patient's reasons for seeking treatment and their expectations, as these factors help clinicians determine whether the benefits of treatment outweigh the risks for each individual. The need to elicit and discuss patient's wishes is instrumental for post-treatment success (Oland et al, 2011); this is particularly important with regards to aesthetics, as patients may perceive themselves differently from how their clinicians see them (Chew et al, 2007). It is well established that post-treatment success is linked to pre-treatment motivation and expectations and that unrealistic wishes may contribute to post-treatment dissatisfaction (Nurminen et al, 1999;Espeland et al, 2008;Oland et al, 2011).…”
Section: Introductionmentioning
confidence: 99%